The Effect of Taxes on Entrepreneurs and Their Decision-Making Process in Germany - Sara Ravan Ramzani; Phungmayo Horam; Ahmad Abu-Alkheil; Sravya Vasa (Citakonsultindo, 2024)
This study investigates the impact of taxes on the decision-making process of entrepreneurs in Germany. Employing a survey methodology, information was gathered from a sample of 500 entrepreneurs who manage small and medium-sized enterprises (SMEs) in Germany. The findings indicate a pivotal role played by taxation in shaping the choices made by entrepreneurs. Elevated tax burdens discourages business owners from making significant investments or venturing into projects characterized by substantial risk. Furthermore, entrepreneurs exhibit a propensity to opt for locations with lower tax obligations when initiating or expanding their enterprises. This study has important implication for German policymakers as high tax rates are identified as potential impediments to entrepreneurship and overall economic growth. The study recommends that tax policy should be designed to foster entrepreneurship and stimulate economic growth. This study investigates the impact of taxes on the decision-making process of entrepreneurs in Germany. Employing a survey methodology, information was gathered from a sample of 500 entrepreneurs who manage small and medium-sized enterprises (SMEs) in Germany. The findings indicate a pivotal role played by taxation in shaping the choices made by entrepreneurs. Elevated tax burdens discourages business owners from making significant investments or venturing into projects characterized by substantial risk. Furthermore, entrepreneurs exhibit a propensity to opt for locations with lower tax obligations when initiating or expanding their enterprises. This study has important implication for German policymakers as high tax rates are identified as potential impediments to entrepreneurship and overall economic growth. The study recommends that tax policy should be designed to foster entrepreneurship and stimulate economic growth. This study investigates the impact of taxes on the decision-making process of entrepreneurs in Germany. Employing a survey methodology, information was gathered from a sample of 500 entrepreneurs who manage small and medium-sized enterprises (SMEs) in Germany. The findings indicate a pivotal role played by taxation in shaping the choices made by entrepreneurs. Elevated tax burdens discourages business owners from making significant investments or venturing into projects characterized by substantial risk. Furthermore, entrepreneurs exhibit a propensity to opt for locations with lower tax obligations when initiating or expanding their enterprises. This study has important implication for German policymakers as high tax rates are identified as potential impediments to entrepreneurship and overall economic growth. The study recommends that tax policy should be designed to foster entrepreneurship and stimulate economic growth. This study investigates the impact of taxes on the decision-making process of entrepreneurs in Germany. Employing a survey methodology, information was gathered from a sample of 500 entrepreneurs who manage small and medium-sized enterprises (SMEs) in Germany. The findings indicate a pivotal role played by taxation in shaping the choices made by entrepreneurs. Elevated tax burdens discourages business owners from making significant investments or venturing into projects characterized by substantial risk. Furthermore, entrepreneurs exhibit a propensity to opt for locations with lower tax obligations when initiating or expanding their enterprises. This study has important implication for German policymakers as high tax rates are identified as potential impediments to entrepreneurship and overall economic growth. The study recommends that tax policy should be designed to foster entrepreneurship and stimulate economic growth. This study investigates the impact of taxes on the decision-making process of entrepreneurs in Germany. Employing a survey methodology, information was gathered from a sample of 500 entrepreneurs who manage small and medium-sized enterprises (SMEs) in Germany. The findings indicate a pivotal role played by taxation in shaping the choices made by entrepreneurs. Elevated tax burdens discourages business owners from making significant investments or venturing into projects characterized by substantial risk. Furthermore, entrepreneurs exhibit a propensity to opt for locations with lower tax obligations when initiating or expanding their enterprises. This study has important implication for German policymakers as high tax rates are identified as potential impediments to entrepreneurship and overall economic growth. The study recommends that tax policy should be designed to foster entrepreneurship and stimulate economic growth. This study investigates the impact of taxes on the decision-making process of entrepreneurs in Germany. Employing a survey methodology, information was gathered from a sample of 500 entrepreneurs who manage small and medium-sized enterprises (SMEs) in Germany. The findings indicate a pivotal role played by taxation in shaping the choices made by entrepreneurs. Elevated tax burdens discourages business owners from making significant investments or venturing into projects characterized by substantial risk. Furthermore, entrepreneurs exhibit a propensity to opt for locations with lower tax obligations when initiating or expanding their enterprises. This study has important implication for German policymakers as high tax rates are identified as potential impediments to entrepreneurship and overall economic growth. The study recommends that tax policy should be designed to foster entrepreneurship and stimulate economic growth. This study investigates the impact of taxes on the decision-making process of entrepreneurs in Germany. Employing a survey methodology, information was gathered from a sample of 500 entrepreneurs who manage small and medium-sized enterprises (SMEs) in Germany. The findings indicate a pivotal role played by taxation in shaping the choices made by entrepreneurs. Elevated tax burdens discourages business owners from making significant investments or venturing into projects characterized by substantial risk. Furthermore, entrepreneurs exhibit a propensity to opt for locations with lower tax obligations when initiating or expanding their enterprises. This study has important implication for German policymakers as high tax rates are identified as potential impediments to entrepreneurship and overall economic growth. The study recommends that tax policy should be designed to foster entrepreneurship and stimulate economic growth.